Vertebrate-Aedes aegypti and Culex quinquefasciatus (Diptera)-arbovirus transmission networks: Non-human feeding revealed by meta-barcoding and next-generation sequencing. - José Guillermo Estrada-Franco; Nadia A Fernández-Santos; Adeniran A Adebiyi; María de J López-López; Jesús A Aguilar-Durán; Luis M Hernández-Triana; Sean W J Prosser; Paul D N Hebert; Anthony R Fooks; Gabriel L Hamer; Ling Xue; Mario A Rodríguez-Pérez (Public Library of Science (PLoS), 2020)
Background Aedes aegypti mosquito-borne viruses including Zika (ZIKV), dengue (DENV), yellow fever (YFV), and chikungunya (CHIKV) have emerged and re-emerged globally, resulting in an elevated burden of human disease. Aedes aegypti is found worldwide in tropical, sub-tropical, and temperate areas. The characterization of mosquito blood meals is essential to understand the transmission dynamics of mosquito-vectored pathogens. Methodology/principal findings Here, we report Ae. aegypti and Culex quinquefasciatus host feeding patterns and arbovirus transmission in Northern Mexico using a metabarcoding-like approach with next-generation deep sequencing technology. A total of 145 Ae. aegypti yielded a blood meal analysis result with 107 (73.8%) for a single vertebrate species and 38 (26.2%) for two or more. Among the single host blood meals for Ae. aegypti, 28.0% were from humans, 54.2% from dogs, 16.8% from cats, and 1.0% from tortoises. Among those with more than one species present, 65.9% were from humans and dogs. For Cx. quinquefasciatus, 388 individuals yielded information with 326 (84%) being from a single host and 63 (16.2%) being from two or more hosts. Of the single species blood meals, 77.9% were from dogs, 6.1% from chickens, 3.1% from house sparrows, 2.4% from humans, while the remaining 10.5% derived from other 12 host species. Among those which had fed on more than one species, 11% were from dogs and humans, and 89% of other host species combinations. Forage ratio analysis revealed dog as the most over-utilized host by Ae. aegypti (= 4.3) and Cx. quinquefasciatus (= 5.6) and the human blood index at 39% and 4%, respectively. A total of 2,941 host-seeking female Ae. aegypti and 3,536 Cx. quinquefasciatus mosquitoes were collected in the surveyed area. Of these, 118 Ae. aegypti pools and 37 Cx. quinquefasciatus pools were screened for seven arboviruses (ZIKV, DENV 1-4, CHIKV, and West Nile virus (WNV)) using qRT-PCR and none were positive (point prevalence = 0%). The 95%-exact upper limit confidence interval was 0.07% and 0.17% for Ae. aegypti and Cx. quinquefasciatus, respectively. Conclusions/significance The low human blood feeding rate in Ae. aegypti, high rate of feeding on mammals by Cx. quinquefasciatus, and the potential risk to transmission dynamics of arboviruses in highly urbanized areas of Northern Mexico is discussed.